STUDI PENGEMBANGAN BUDIDAYA IKAN SISTEM KOLAM AIR DERAS DI SUNGAI CARAMELE KOTA PAREPARE SULAWESI SELATAN - Khairuddin, Khairuddin; Munir, Munir (Journal Galung Tropika, 2012)
Caramele river as upper of karajae river in the parepare city potencial development running water fish pond culture and integrated of tourism and environment sustainability resource. This aimed study to evaluated technical and non technical feasibility aspect arounded karajae river for running water fish pond system. The study used purpose sampling method and variable investigated include; (1) water quality (temperature, velocity, vegetation, soil texture, bentic organism, oxygen,pH,accesability, etc.), (2) environment and social economic impact for native people in the around area. Investigation area fixed three station. The result of the study revealed that feasibility each stations appromixately are Station I (71,3%), Station II (71,3%) and Station III (71,0%). The stations feasibility for development of running water fish pond system are Station I and II.